2015
DOI: 10.1121/1.4906165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fiber orientation on the inherent acoustic nonlinearity in carbon fiber reinforced composites

Abstract: This paper presents the study of non-classical nonlinear response of fiber-reinforced composites. Nonlinear elastic wave methods such as nonlinear resonant ultrasound spectroscopy (NRUS) and nonlinear wave modulation spectroscopy have been used earlier to detect damages in several materials. It was observed that applying these techniques to composites materials becomes difficult due to the significant inherent baseline nonlinearity. Understanding the non-classical nonlinear nature of the composites plays a vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Chakrapani et al reported the inherent NCNL response of composites using the NRUS technique. 22 The influence of fiber orientation on the NCNL response was studied in intact UD CFRP laminates by varying the fiber orientation along the length of the sample. The current article builds on the previous work by the authors 22 in terms of characterizing the effect of laminate sequence and fabric type on the NCNL response.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chakrapani et al reported the inherent NCNL response of composites using the NRUS technique. 22 The influence of fiber orientation on the NCNL response was studied in intact UD CFRP laminates by varying the fiber orientation along the length of the sample. The current article builds on the previous work by the authors 22 in terms of characterizing the effect of laminate sequence and fabric type on the NCNL response.…”
Section: Introductionmentioning
confidence: 99%
“…22 The influence of fiber orientation on the NCNL response was studied in intact UD CFRP laminates by varying the fiber orientation along the length of the sample. The current article builds on the previous work by the authors 22 in terms of characterizing the effect of laminate sequence and fabric type on the NCNL response. The NCNL characteristics of four different laminate sequences were investigated and they were compared to the results obtained from the previous orientation study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear (resonant frequencies and quality factor), and nonlinear hysteretic parameters corresponding to first bending and longitudinal modes of vibration were investigated. (Chakrapani, Barnard, & Dayal, 2015). Under dynamic loading, the nonlinear behavior arises from the interfacial friction, debonding, and subsequent interfacial slip between fibers and matrix (Nelson & Hancock, 1978).…”
Section: Discussionmentioning
confidence: 99%